Jurassic-Paleogene spreading history of the northern Indian Ocean as a constraint on the evolution of the north Australia continental margin - Charlton, Tim R. (Berita Sedimentologi, 2023)
The spreading history of the northern Indian Ocean is re-examined with the aim of interpreting the late Mesozoic-Paleogene evolution of the northern Australian continental margin in eastern Indonesia and Timor-Leste. The earliest seafloor spreading (‘Argo phase’) developed between approximately 155-131Ma (Kimmeridgian, Late Jurassic to Valanginian, Early Cretaceous). A clockwise pole of rotation relative to Australia (‘Argo pole’) is interpreted at 7°09’S, 133°07’E, a present-day location near the Tanimbar islands in eastern Indonesia. A second ‘Gascoyne’ phase of spreading, between 131-100Ma (late Early Cretaceous), had an interpreted clockwise rotation pole at 3°40’N, 125°00’E, a present-day location between the islands of Mindanao (southern Philippines) and Sulawesi (eastern Indonesia). A third ‘Wharton’ phase of spreading, commencing at the beginning of the Late Cretaceous (~100Ma) had a more distant pole (clockwise pole at 5°S, 171°E: Jacob et al., 2014), although more local rotations are interpreted for the Greater Sula Spur continental terrane, about a pole estimated at 9°24’S, 134°40’E, close to the earlier Argo pole.The motions of two continental terranes are inferred from the spreading history. The Argoland Terrane, which is identified in this study as eastern Sundaland (Borneo and Java), would not have entirely detached from Australia before the mid Cretaceous due to the relatively proximal locations of the Argo and Gascoyne rotation poles. In this scenario Argoland could not have collided with Eurasia in the Cretaceous, as suggested by several previous studies. The Greater Sula Spur Terrane (several continental fragments in present-day eastern Indonesia), is repositioned in the initial reconstructions immediately north of Timor, and did not move northward to its late Paleogene (pre-Neogene collision) location until the Wharton phase of rifting that commenced in the Late Cretaceous. This northward motion of the Greater Sula Spur was accommodated by the development of a narrow oceanic basin (the Banda Embayment).The reconstructions suggest that the Argoland and Greater Sula Spur continental terranes formed a continuous crustal connection between SE Asia and northern Australia throughout the late Mesozoic and early Paleogene, and that the Indian Ocean developed entirely within the body of the disrupting Gondwanaland supercontinent, rather than linking eastwards into the Pacific Ocean.